Combination of interferon alfa-2b and ribavirin in relapsed or nonresponding chronic hepatitis C patients following interferon therapy (Medical Journal of Indonesia, 2001)
Twenty six patients (pts) with chronic hepatitis C (CHC) who reLapsed or non-responded following.interferon (IFN) therapy were given lFN alfa-2b 3 MIU three times a week for 48 weeks in combination with Ribavirin 800-1000 mg daily 2I (80,8%) of the 26.pts completed the study consisted of 12 relapsers and 9 non-responders. Five pts dropped out due to drug adverse events in three pts and non-drug related reason in the other two. In the relapsed group complete response, relapse and sustained response rates were obtained in 9/12(75%), 2/2 (16,5%) and 7/12(58,3%) pts respectively. In the non- responding group, these figures were 3/9 (33,3%), 1/9(I1,1%), and 2/9(22,2%) pts, respectively. The most frequent adverse event was flu-like syndrome, which was found in 18 pts (85,7%). Combination therapy of IFN alfa-2b and ribavirin may induce sustained virological response in relapsed and non-responding CHC patients. This combination therapy is more effective for relapsers compared to for non-responders. (Med J Indones 2001; 10: 214-8)